Work Motivation and Employee Performance in The Service Industry: The Mediating Role of Work Discipline - Dewi, Ananda Fitriani; Zainuddin; Pakpahan, Efendi (International Journal of Accounting and Economics Studies, 2026)
From an economic perspective, these findings have direct implications for labor productivity, operational efficiency, and service-sector competitiveness, as enhanced employee motivation and disciplined behavior can reduce service delivery costs while improving customer satisfaction and revenue generation. This study examines how individual, developmental, environmental, and cultural factors jointly shape employee performance in a standardized service setting. Drawing on Job Demands–Resources and Self-Determination Theory, the model positions work motivation, work discipline, career development, work environment, and organizational culture as predictors of employee performance, with work motivation as a central psychological mechanism. Data were collected from frontline employees in a standardized service organization and analyzed using partial least squares structural equation modeling (PLS-SEM). The results show that work motivation is the strongest predictor of employee performance, followed by work discipline, career development, work environment, and organizational culture. Work motivation also mediates the effects of career development, work environment, and organizational culture on performance, indicating that organizational resources enhance performance primarily by strengthening employees’ motivational states. The model demonstrates substantial explanatory power for employee performance and satisfactory predictive relevance and global model fit. These findings extend existing organizational behavior, service management, and HRM literature by integrating motivational, developmental, environmental, and cultural perspectives into a unified behavioral model of performance in standardized service operations. Practically, the results highlight the need for organizations to design HR systems and managerial practices that simultaneously foster work motivation, reinforce disciplined behavior, provide developmental opportunities, cultivate supportive cultures, and maintain adequate work environments to sustain high levels of frontline performance.
Keywords: Employee Performance, Work Discipline, Work Motivation, Career Development, Work Environment, Organizational Culture